Ontological Constraints in Children's Inductive Inferences: Evidence From a Comparison of Inferences Within Animals and Vehicles - Tarlowski, Andrzej (Frontiers in Psychology, 2018)
There is a lively debate concerning the role of conceptual and perceptual information in young children’s inductive inferences. While most studies focus on the role of basic level categories in induction the present research contributes to the debate by asking whether children’s inductions are guided by ontological constraints. Two studies use a novel inductive paradigm to test whether young children have an expectation that all animals share internal commonalities that do not extend to perceptually similar inanimates. The results show that children make category-consistent responses when asked to project an internal feature from an animal to either a dissimilar animal or a similar toy replica. However, the children do not have a universal preference for category-consistent responses in an analogous task involving vehicles and vehicle toy replicas. The results also show the role of context and individual factors in inferences. Children’s early reliance on ontological commitments in induction cannot be explained by perceptual similarity or by children’s sensitivity to the authenticity of objects.